Deposition of Hyperphosphorylated Tau in Cerebellum of PS1 E280A Alzheimer’s Disease (2011)
ABSTRACT: Early-onset familial Alzheimer’s disease (AD) caused by presenilin-1 mutation E280A (PS1-E280A) presents wide clinical and neuropathological variabilities. We characterized clinically and neuropathologically PS1-E280A focusing in cerebellar involvement and compared it with early-onset sporadic Alzheimer’s disease (EOSAD). Twelve E280A brains and 12 matched EOSAD brains were analyzed for beta-amyloid and hyperphosphorylated tau (pTau) morphology, beta-amyloid subspecies 1–40, 1–42 levels, pTau levels, and expression of stress kinases in frontal cortex and cerebellum. The data were correlated to clinical and genetic findings. We observed higher beta-amyloid load, beta-amyloid 1–42 and pTau concentrations in frontal cortex of PS1-E280A compared with EOSAD. High beta-amyloid load was found in the cerebellum of PS1-E280A and EOSAD patients. In PS1-E280A, betaamyloid localized to the molecular and Purkinje cell layers, whereas EOSAD showed them in Purkinje and granular cell layers. Surprisingly, 11 out of 12 PS1-E280A patients showed deposition of pTau in the cerebellum. Also, seven out of 12 PS1-E280A patients presented cerebellar ataxia. We conclude that deposition of beta-amyloid in the cerebellum is prominent in early-onset AD irrespective of genetic or sporadic origin. The presence of pTau in cerebellum in PS1-E280A underscores the relevance of cerebellar involvement in AD and might be correlated to clinical phenotype.